TINJAUAN KEGIATAN WORLD WIDE FUND FOR NATURE (WWF) DALAM KONSERVASI KEANEKARAGAMAN HAYATI (Studi Kasus: Konservasi Penyu Hijau Di Pantai Pangumbahan, Sukabumi, Jawa Barat Tahun 2015-2018). - Anggraini Kusuma Wardani (2020)
Sea turtles become one of the animals whose population continues to decline and their existence is threatened by various factors, ranging from nature to humans. One of the turtle nesting sites in Indonesia is Pangumbahan Beach, West Java, however the presence of sea turtles in this region continues to be threatened due to lack of information about sea turtles and many people still sell turtle eggs to meet their daily needs, seeing this World The Wide Fund for Nature (WWF), which is one of the international organizations that focus on protecting nature, is directly involved in helping the government cope with the decline in the turtle population that continues to occur every year. This research will discuss about the roles carried out by WWF in Pangumbahan Beach, West Java, the writer will use international organization theory to help the writer examine the data with data collection techniques used are observation, interviews and literature study. The results of this study show WWF has carried out its role well but due to internal factors, the area still needs to be reorganized.